Breakthrough in the social research on childhood: search for the methodology of interdisciplinarity - Juodaitytė, Audronė; Malinauskienė, Daiva; Babić, Nada (Social Welfare: Interdisciplinary Approach, 2019)
Recently in the sciences of social-humanitarian character (education science, sociology, cultural anthropology, psychology, political science, etc.) the methodological breakthrough has taken place. Therefore, the concept of childhood was started being conceptualized in the contexts of the sociocultural discourses of these sciences. Referring to the diversity of the existing opinions about childhood (ecological, cultural, sociological, etc.), the field of talking about its meanings is encountered in various sciences. It is similar to inter-directional negotiations taking place between natural sciences and social-humanitarian sciences. There is a search for all kinds of knowledge permitting to harmonize the approaches existing in sciences and develop the criticism of traditional approaches. It is interdisciplinary negotiations in research that become the practice of the birth of new knowledge about childhood and its sociocultural expression.